On the Bankruptcy Situations and the Alexia Value - S. Z. Alparslan Gök; A. Sarıarslan (Journal of Applied Mathematics)
The main result of this paper is to show that the three ancient bankruptcy situations from the 2000-year-old Babylonian Talmud can be solved by using the average lexicographic value (Alexia) from cooperative game theory.